Thermal conductivity of Ionic Liquids: An estimation approach - Albert, Johannes; Müller, Karsten (Chemical Engineering Science, 2014)
Knowledge about the thermal conductivity of Ionic Liquids can be essential for research and process development. To compensate missing experimental data an estimation approach has been developed. Independency of other, also often unknown, substance properties was a major claim to this work. A structure interpolating approach was chosen assigning contributions to thermal conductivity to the ions. 375 Experimental data points for 39 Ionic Liquids have been collected and used for the development. The data for substances not used for the fitting could be estimated with an average absolute error of 4.99% (the error for substances used for parameter fitting was only 1.21%). A detailed error analysis resulted in a combined experimental and predictive uncertainty of 7.96% for unknown Ionic Liquids. Based on the proposed correlation a systematic screening of Ionic Liquids concerning thermal conduction is possible. © 2014 Elsevier Lt
Keywords: Group contribution method; Ionic Liquids; Prediction; QSPR; Thermal conductivity